Royal responsibility in Anglo-Norman historical writing - Winkler, Emily A. 1986- (Oxford historical monographs, 2017)
It has long been established that the crisis of 1066 generated a florescence of historical writing in the first half of the 12th century. Emily A. Winkler presents a new perspective on previously unqueried matters, investigating how historians' individual motivations and assumptions produced changes in the kind of history written across the Conquest. She argues that responses to the Danish Conquest of 1016 and the Norman Conquest of 1066 changed dramatically within two generations of the latter conquest. Repeated conquest could signal repeated failures and sin across the orders of society, yet early 12th-century historians in England not only extract English kings and people from a history of failure, but also establish English kingship as a worthy office on a European scale